Tradução, adaptação e avaliação psicométrica da Prova Cognitiva de Leganés em uma população idosa brasileira com baixo nível de escolaridade - Caldas, Vescia Vieira de Alencar (2011)
Introdução: The scales of cognitive screening are important tools for early detection of dementia, creating the possibility of developing measures to slow this process and assist in the management of the disease. Objective: To validate the Leganés Cognitive Test (Prueba Cognitive de Leganés) (PCL) for cognitive screening in low educated elderly Brazilians. Methods: The study sample was composed of 59 elderly residents from the city of Santa Cruz, Brazil with low schooling levels. Reliability was analyzed with a 2-day interval between assessments, and concurrent validity was assessed using the Mini Mental State Examination (MMSE). Results: According to the PCL, the prevalence of dementia was 11.8%. The scale items showed a moderate to strong correlation between domains (p <0.01), and inter-rater reliability exhibited ICC = 0.81, 95% CI (0.72-0.88). Factor analysis resulted in two factors: memory and orientation. Interscale agreement was considered poor (k = - 0.02), supporting the hypothesis of an educational impact on final MMSE scores. Conclusion: The results suggest that PCL has acceptable levels of reliability for use in low educated elderly Brazilians